Passage Europe : Realities, References. : A Certain Look at Central and Eastern European Art. - Blazevic, Dunja; Boulatov, Erik; Degot, Jekaterina; Zoran, Eric; Fuchs, Rainer; Hegyi, Lóránd; Landréat, Anne; Makovic, Zvonko; Meyric Hughes, Henry; Sevcik, Jiri (Saint-Etienne : Musée d'Art Moderne de Saint-Etienne Métropole, 2004)
Sýkora, Zdenek ; Filko, Stano ; Opalka, Roman ; Kabakov, Ilya ; Kolar, Jiri ; Knifer, Julije ; Boulatov, Erik ; Dimitrijevic, Braco ; Abramovic, Marina ; Milunovic, Mihael ; Dakic, Danica ; Bajevic, Maja ; Kisseleva, Olga ; Seric-Soba, Nebojsa ; Dokoupil, Jiri Georg ; Potrc, Marjetica ; Jokanovic Toumin Dean ; Lakner, Antal ; Kozaric, Ivan ; Nadler, Istvan ; Malich, Karel ; Hencze, Tamas ; Balka, Miroslav ; Kipke, Zeljko ; Solakov, Nedko ; Kelemen, Karoly ; Mancuska, Jan ; Lehocká, Denisa ; Tarasewicz, Leon ; Koncz, András ; Hlavina, Tomás ; Cernicky, Jiri ; Feher, Laszlo ; Kameric, Sejla ; Perjovschi, Dan ; IRWIN ; Kulundzic,Andreja ; Jaros, Piotr ; Suljevic, Alma ; Németh, Ilona ; Poljak, Renata ; Surúvka, Jiri ; Djuric, Uros ; Kulik, Oleg ; Andjelic-Galic, Gordana ; Franke, Ivana ; Krkobabic, Miodrag ; Radic, Jelena ; Kaludjerovic, Dejan ; Pechoucek, Michal ; Ponomarev, Alexander ; Khoroshilova, Anastasia ; Azorro ; Bakowski, Kuba ; Bergamot ; Niesterowicz, Anna ; Wójcik, Julita ; Zmijewski, Artur ; Kotik, Jan ; Alvaer, Jesper ; Ruka, Inta ; Semper, Ene-Liis ; Revesz, Laszlo ; Binder, Erik ; Pinczehelyi, Sandor
Engels
Exhibition. Passage Europe. Musée d'Art Moderne de Saint-Etienne Métropole. 15.5.2004 - 5.9.2004
boek
Keywords: Oost-Europa